The philosophy of B. Pascal and modern Christian theology. Towards an assessment of Christianity's adaptive capabilities in the postmodern socio-cultural context - Pronyakin , Volodymyr (Sententiae, 2000)
Author claims that Western theology must turn to Pascal's religious-philosophical legacy in order to find identification normatives that can ensure the cultural-adaptive stability of Christian identity. Such an approach is justified by a number of specific features of Pascal's philosophy: (1) existential character of thought; (2) anthropological nature; (3) symbolism; (4) semiotically obvious authenticity of artefacts of religious experience. In the author's opinion, the most promising in this context would be to address (2), Pascal's symbolic metaphysics, which is determined by the predominant influence of the ethical on its ontological and epistemological aspects. However, in the author's opinion, in the polycentric and pluralistic cultural and sociogenic environment of postmodernity, the identificational adaptation of Christianity is not only a "final transition" to religious symbolism. It is also important that Christians effectively strive to preserve and constantly cultivate the ability to value-based worldview.